Religious freedom in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Religious Studies at Massey University - Saunders, Glenice Byrl (Massey University, 2001)
A new conception of religious freedom in New Zealand, a result of both external and internal influences, has largely replaced the old, though signs of transition are still apparent. The old conception, in keeping with its Christian history, was founded on an unwritten understanding by which the state endorsed no particular religion, and stood apart from sectarian rivalry. This has now fallen away with increasing secularization, social change, pluralism and the development of human rights discourse. Public perceptions of religion are broadening to include other faiths apart from Christianity, such as indigenous belief; it can be acknowledged that Maori also experienced colonization, especially the loss of land, as an assault on their religious freedom. Each of the last three decades saw an adjustment in state policy which reflected these changes and involved the state in a more active role regarding religion, so altering the nature of religious freedom. These were, in order, the integrating of most religious schools into the state education system, the embracing of biculturalism, and the passing of new constitutional legislation (the Bill of Rights Act and the Human Rights Act). Examining what has been written (mainly by lawyers) on freedom of religion since the last of these revealed a range of reactions, in part determined by the authors' personal attitudes to religion which were able to be uncovered by using a Religious Studies perspective. Little has been written from within the discipline of Religious Studies on the implications of the above changes for religion. Because the new conception of religious freedom is based on individual autonomy, it is displacing the authoritarian model of parenting and teaching; this is difficult for those who wish to retain the old model for religious reasons. Since religious freedom is now based on respect for the beliefs of others, whether 'religious' or not, rather than on the absence of state interference in religion, the way is open for the teaching in schools of courses about religion and belief to prepare children better for life and for living in a pluralist society.
Keywords: New Zealand; Freedom of religion; Church and state